Towards a global geopolitical novum – with or without World War until a change of order? - Stepic, Milomir (Sociološki pregled, 2026)
The world is undergoing a turbulent transition between different orders, which is manifested through political, military, technological, economic, religious, propaganda, and other confrontations. The participants in the said conflicts are actors who are striving to perpetuate a privileged status quo, on the one hand, and rising powers with aspirations to change the system in which their position is inferior, on the other. Although armed conflicts may at first glance have a proxy character, a world war is possible as multiple simultaneous regional wars. The author argues that the outcomes of such wars are already yielding a geopolitical, i.e., comprehensive reshaping of the world. Absolute domination of the US during the “unipolar moment” ceased to exist a long while ago, whereas a multipolar system in its true sense has not yet been fully established. The current historical-geopolitical situation would be the most accurately defined as a process of multipolarisation, that is, a process of structuring a polycentric world. For the time being, it is impossible to say what this polycentricity will look like, what the alignment of powers will be on the scale of global power, and whether they will incline towards at least a passable balance of (neo) bipolarity. Additionally, there is another “end of history”(?) on the horizon, with an imminent shifting of the earlier unipolarity towards a new one – Pax Americana will be followed by an attempt to establish Pax Sinica. Therefore, general thinking does not go beyond the set patterns of coordinates of some form of polarity. Nevertheless, there is ample indication that there is an ongoing shifting towards a new geopolitical novum – mosaic-like structure of building blocks whose principles of integration will be fragmented, with fluid borders, while connections will be flexible.